OC-055 Blood-Based Biomarkers in the Oesophageal Cancer Model – Results from the PigA Mutant Phenotype Study. (17th August 2016) - Haboubi, HN; Williams, L; Manson, J; Al-Mossawi, N; Rees, B; Lawrence, R; Bodger, O; Griffiths, P; Thornton, C; Jenkins, GJ
Abstract : Introduction: Improving our mechanisms of risk stratification of patients with Barrett's oesophagus (BO) requires easily analysable, cheap and reproducable biomarkers. The PigA mutant phenotype assay is a novel flow cytometric analysis, which can be undertaken using a fingerprick test. The PigA gene codes for GPI-anchors, which tether proteins to the surface of circulating blood cells. Silencing mutations, induced by acid or bile, will therefore result in absence of surface GPI-anchors and negative fluorescence on flow cytometry analysis. Our laboratory has already demonstrated the effects of bile in inducing such "mutant" events in blood based cell lines. Methods: Here, we investigate the baseline background PigA mutant phenotype frequency in patients with GORD, BO, and those with oesophageal adenocarcinoma (OAC). We recruited 120 patients for analysis of baseline mutant frequency in circulating red blood cells. We correlated these findings with symptoms, diet, lifestyle, endoscopic features and radiological stage. We also undertook Western Blotting analysis of endoscopic biopsies to assess GPI-anchor status in retrieved tissue. Results: A clear correlation was seen with increased PigA mutant frequency with histological status from healthy patients with GORD to those with OAC, p < 0.01. Older age, smoking status and unhealthy lifestyle (diet measured using the DQS score) all resulted in higher mutant frequencies. Length of Barrett's and degree of inflammation (LA classification) had no effect, but aspirin use appeared to be protective and resulted in lower mutant frequencies (p < 0.01). Evaluation of patients with cancer (n = 15) found that PigA mutant frequency increased with increasing lymph node involvement and metastasic spread (both p < 0.001). Finally western blotting of crude protein extracted from oesophageal biopsies revealed a reduction in GPI-anchor levels from normal squamous tissue, through to cancer, thus corroborating our results above. Conclusion: We have developed a blood-based biomarker assay, which can potentially stratify patients' underlying genomic instability by indirectly measuring GPI-anchor status on circulating blood cells. We have also demonstrated the potential onco-protective effects of aspirin in these patients. The mechanisms behind these observations remain unclear, but western blot analysis suggests mutation may occur in the distal oesophagus where circulating blood cells are exposured to mutagenic chemicals such as bile and acid. Further evaluation in other cancer models as well as a wider cohort of non-cancer patients (to evaluate lifetyle) will establish how useful the assay may be outside of the Barrett's model. Disclosure of Interest: None Declared